Pemanfaatkan Lingkungan Alam Pesisir sebagai Media Pembelajaran Geografi untuk Optimalisasi Hasil Belajar Siswa di MAN 1 Majene - Suharni, Suharni; Hasriyanti, Hasriyanti; Maddatuang, Maddatuang; Syarif, Erman; Al Ghani, Muhammad Zulfi (UNIVERSITAS NEGERI MAKASSAR, 2025)
The surrounding environment of students serves as an important learning resource that can be utilized in the learning process. This study offers a solution by applying contextual geography learning using the coastal environment as a learning laboratory, considering that the school is located in a coastal area. Using a Nonequivalent Control Group Design, the research was conducted over three sessions involving Class Xb as the experimental group and Class Xc as the control group at MAN 1 Majene. Environmental-based learning was implemented in the experimental group through direct observation around the school, while the control group used conventional methods. Post-test results showed that the experimental group achieved a higher average score of 80.19 with a standard deviation of 7.781. Additional assignments, such as observation reports and group presentations, further enhanced students’ analytical skills. The findings indicate that environmental-based learning is more effective in improving students’ understanding of biosphere material compared to traditional approaches.